Pengaruh Disiplin Kerja, Motivasi dan Pengembangan Karier terhadap Kinerja Pegawai Negeri Sipil pada Pemerintah Kabupaten Tabalong di Tanjung Kalimantan Selatan - ., M. Harlie (Universitas Brawijaya, Indonesia, 2012)
Effort in building state apparatur as human resourses in goverment organisation has on important role in deciding success of development in general, as an effort to give prosperity to commenity and giving the best service. To do this of course we need to raise up the quality of apparatur, so they can do their job well to enchange goal achievement. Because of that the state apparatur should have some characteristics, namely , high expertise and skill, a wide knowledge, good talent potential, personality, motivation,morality and work ethic. To equire there characteristics, the apparatur should develop their potential by providing education and training programing based on their field of expertise. The system of work motivationand career development should be done in this case.This research study and analyze on the influence of work dicipline, motivation and career development,toward work ethic of civil servant at goverment of Tabalong regency, South Kalimantan.